Prevention of diabetes and cardiovascular disease in patients with impaired glucose tolerance: rationale and design of the Nateglinide And Valsartan in Impaired Glucose Tolerance Outcomes Research (NAVIGATOR) Trial. - Califf, R; Boolell, M; Haffner, S; Bethel, M; McMurray, J; Duggal, A; Holman, R (2008)
Patients with impaired glucose tolerance (IGT) have increased risk for developing type 2 diabetes mellitus (T2DM) and cardiovascular disease (CVD). Lifestyle modification and medication can prevent or delay progression to diabetes (PD), but whether such interventions also reduce the risk of CVD has not been rigorously tested. The Nateglinide And Valsartan in Impaired Glucose Tolerance Outcomes Research (NAVIGATOR) trial is a multinational, randomized, double-blind, 2 x 2 factorial trial in subjects with IGT (on a screening oral glucose tolerance test [OGTT]) aged > or = 50 years with known CVD or aged > or = 55 years with > or = 1 CVD risk factor. Enrollment began in January 2002 and was completed January 2004, with 9,518 patients randomized to receive 1 of 4 possible treatment combinations as follows: nateglinide with valsartan, nateglinide with valsartan-placebo, nateglinide-placebo with valsartan, or nateglinide-placebo with valsartan-placebo. All subjects are participating in a clinic-based and telephone-based lifestyle intervention aimed at reducing weight and dietary fat and increasing physical activity. The 3 coprimary end points are new onset of T2DM, a "core" composite of major cardiovascular events (death, myocardial infarction, stroke, or hospitalization for heart failure), and an "extended" composite including the components of the core composite plus coronary revascularization and hospitalization for unstable angina. The study was designed to evaluate whether reducing postprandial hyperglycemia, blockade of the renin-angiotensin-aldosterone system, or both interventions reduce the risk of T2DM or cardiovascular events in patients with IGT.